Growth and volume based on permanent sample plots in forests managed by communities - Puri, L.; Meilby, H.; Rayamajhi, S.; Timilsina, Y. P.; Gautam, N. P.; Subedi, R.; Larsen, H. O. (Banko Janakari, 2013)
In order to monitor the woody biomass yield 241 permanent sample plots wereestablished in four forests (total 2017 ha) across three physiographic regionsof Nepal. Tree species identification, tree positioning and diameter at breastheight (DBH) for all trees and height for a sample of trees were measured in2005 and 2010. Results presented are density and volume by forest, speciesand diameter class in 2010 and the species-wise increment between 2005and 2010 by forest. Standing volumes were between 134 and 311 m3ha-1, andannual volume increment was 2.5-7.6 m3ha-1. These plots may be utilized forfuture research, teaching and for local planning purposes. DOI: http://dx.doi.org/10.3126/banko.v22i2.9194 Banko Janakari: A Journal of Forestry Information for Nepal Vol. 22, No. 2, 2012 November Page: 11-18 Uploaded date: 12/1/2013